2021
DOI: 10.1007/s10597-021-00919-1
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Accessing Mental Health Services by Migrant Youth

Abstract: The purpose of the study was to identify barriers to accessing mental health services by migrant youth in a middle-sized central Canadian city. We asked participants, "What would stop you from talking to someone about mental health stress?". We interviewed 30 youth aged 16 to 22 who migrated from 10 different countries and lived in Canada for an average of 29 months. The data was analyzed using group concept mapping. The participants identified five concepts: fear of being misunderstood or ignored, desire for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…marginalized and stigmatized groups), which includes children and newcomer families (Burgos et al, 2019; Cook & Bergeron, 2019). For example, Finnigan et al (2021) found concept mapping to be an effective methodology for engaging newcomer youth in research on understanding their barriers to accessing mental health services in a new country and Nowicki and Brown (2015) noted that concept mapping can be used to engage children to share their perspective and expertise. While concept mapping has been shown to be effective for use with hard‐to‐reach communities, such as newcomers and youth, this approach has not yet been utilized to examine the perspective of Yazidi youth refugees.…”
Section: Methodsmentioning
confidence: 99%
“…marginalized and stigmatized groups), which includes children and newcomer families (Burgos et al, 2019; Cook & Bergeron, 2019). For example, Finnigan et al (2021) found concept mapping to be an effective methodology for engaging newcomer youth in research on understanding their barriers to accessing mental health services in a new country and Nowicki and Brown (2015) noted that concept mapping can be used to engage children to share their perspective and expertise. While concept mapping has been shown to be effective for use with hard‐to‐reach communities, such as newcomers and youth, this approach has not yet been utilized to examine the perspective of Yazidi youth refugees.…”
Section: Methodsmentioning
confidence: 99%
“…The coding network is represented by the standard neural network function passed through an activation function where z is the hidden dimension. (12) Similar to the way of identifying the encoding network, the decoding network can also be represented using various weights, biases, and potential activation functions. (13) The loss function may then be expressed in terms of these network functions, and Equation ( 14) contains the function that is utilized to train the neural network using the common backpropagation method [20].…”
Section: Deep Autoencoder Networkmentioning
confidence: 99%
“…They range from the limited literacy level of health service users, cultural differences, age-related physical and cognitive changes, emotional states affecting the ability to listen, learn, and remember, insufficient time allocated for the doctor-patient relationship, the emotional state of the patient or the person who wants to receive information (fear, pain, etc. ), the complexity of the diagnostic process of constantly renewed and increasing research findings [12]. It has been determined that immigrants, who are among the risky groups, have difficulties while benefiting from health services [13].…”
Section: Introductionmentioning
confidence: 99%